1978
DOI: 10.1073/pnas.75.10.5132
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid dendritic cells are potent stimulators of the primary mixed leukocyte reaction in mice.

Abstract: Dendritic cells (DCs) are a new cell type initially identified in mouse Iymphoid organs. Recently, DCs have been purified from mouse spleen. This paper demonstrates a functional role of DCs: they are potent stimulators of the primary mixed leukocyte reaction (MLR). As few as 300-1000 DCs doubled the proliferative activity of 5 X 106 allogeneic responder spleen cells, while 0.3-1.0 X 10A DCs induced a maximal stimulation of 30-to 80-fold. Between these extremes, the log of the MLR response increased linearly wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
349
0
11

Year Published

1981
1981
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 670 publications
(373 citation statements)
references
References 24 publications
13
349
0
11
Order By: Relevance
“…12,13 Cell-cell interactions are reduced in cells transcyte reactions (MLR). 20,21 To assess in part the function of fected with the MUC1 cDNA. 14 Other work has Ad-transduced DC, we compared their effects in primary demonstrated that DF3 inhibits the recognition of targets allogeneic MLR with those obtained from non-transby immune effector cells.…”
Section: Are Functional In Inducing Antitumor Immunity Dendritic mentioning
confidence: 99%
“…12,13 Cell-cell interactions are reduced in cells transcyte reactions (MLR). 20,21 To assess in part the function of fected with the MUC1 cDNA. 14 Other work has Ad-transduced DC, we compared their effects in primary demonstrated that DF3 inhibits the recognition of targets allogeneic MLR with those obtained from non-transby immune effector cells.…”
Section: Are Functional In Inducing Antitumor Immunity Dendritic mentioning
confidence: 99%
“…Purification of the co-polymer was achieved by precipitation in acetone followed by removal of residual solvent via vacuum pump (24 h). Confirmation of the co-polymerization was assessed by 1 H NMR analysis and the DP was determined by GPC analysis. Conversion rate of the RAFT polymerization was achieved by 1 H NMR analysis of the reaction mixture at different time points.…”
Section: Dynamic Light Scattering (Dls)mentioning
confidence: 99%
“…1,2 This discovery has led to major insights in how the immune system interacts with foreign material, revealing dendritic cells as the critical factor in the interplay between the innate and the adaptive immune response. 3,4 DCs are the most potent class of antigen presenting cells (APCs) of the immune system and have the capacity to efficiently recognize pathogens, process and present these foreign antigens to T-lymphocytes leading to activation and proliferation of adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Découverte en 1973 par Ralph Steinman et Zanvil Cohn [1], cette cellule accessoire -arborisée en prolongements mobiles -fut nommée « dendritique » (nom dérivé du grec dendreon) (Figure 1). Elle fut rapidement reconnue comme une cellule stimulatrice puissante des réactions lymphocytaires mixtes traduisant une incompatibilité du système HLA in vitro [2] et comme une cellule jouant un rôle central dans les mécanismes de rejets de greffons rénaux chez le rat (1982). Cette découverte fondamentale de l'immunologie cellulaire a permis de comprendre le lien existant entre immunité innée (ou immédiate, ne nécessitant pas la génération et la sélection de récepteurs spécifiques de l'antigène et dépourvue de mécanismes de « mise en mémoire » de l'antigène) et immunité adaptative rouges de mouton dans les rates de souris, R. Steinman et Z. Cohn ont identifié morphologiquement une cellule rare, stellée, radiorésistante, sans laquelle la réponse immunitaire contre ces globules rouges ne pouvait avoir lieu.…”
unclassified
“…Les preuves expérimentales de l'activité présenta-trice d'antigènes des cellules dendritiques in vivo furent apportées grâce à l'utilisation des modèles de transplantation rénale et pancréatique : la déplétion de ces cellules dendritiques par un anticorps produit dans le laboratoire de R. Steinman [5] réduisait ou prévenait le rejet du greffon [6,7]. Ce rôle central joué par la cellule dendritique dans les mécanismes de rejet était la traduction in vivo de ce que Ralph Steinman avait parallèlement démontré in vitro : la mise en évidence de l'extraordinaire capacité de ces cellules à induire une réponse proliférative des lymphocytes T allogéniques (provenant d'un autre individu différant par ses molécules du CMH) in vitro [2] et de son rôle central dans ce phénomène [8]. Il fallut ensuite quinze ans de recherches assidues dans le domaine pour que la cellule dendritique soit utilisée en routine dans les tests de proliféra-tion in vitro (test de réaction lymphocytaire mixte ou MLR).…”
unclassified